Occurrence, and sources of persistent organic pollutants in upper urban soil of Cluj-Napoca, Romania - HERGHELEGIU, Mihaela-Cătălina; PĂNESCU, Vlad-Alexandru (Studia Universitatis Babeș-Bolyai Ambientum, 2023)
Most persistent organic pollutants (POPs) were made for specific purposes due to certain characteristic and properties. They can cause various diseases and are problematic for the environment due to their high persistence and toxicity. This study attests the presence of three classes of POPs namely polycyclic aromatic hydrocarbons (PAHs), organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) in the upper urban soils of Cluj-Napoca, Romania. Soil samples were collected from 10 sampling points areas with heavy traffic. For determination of the compounds, gas chromatography coupled with mass spectrometry and with electron capture detector was used. The obtained results indicate a low level of pollution, the concentrations ranging between 8.83–184.92 ng/g for PAHs, 5.36–112.35 ng/g for PCBs, and 25.96–334.83 ng/g for OCPs. To identify the pollution emission sources, different PAHs and OCPs diagnostic ratios have been applied.